Cellular quiescence: How TGFβ protects cancer cells from chemotherapy - Jessie A Brown; Markus Schober (Molecular & Cellular Oncology, 2018)
Using a functional proliferation reporter we identified quiescent tumor propagating cancer cells (TPCs) in intact squamous cell carcinomas, and found that TGFβ signaling controls their reversible entry into a growth arrested state, which protects TPCs from chemotherapy. TPCs with compromised TGFβ/Smad signaling can't enter quiescence and subsequently die from chemotherapy.